Cognitive, Behavioral, and Situational Influences on Relapse to Smoking After Group Treatment for Tobacco Dependence - Lunden, Sara E.; Pittman, Jami C.; Prashad, Neelam; Malhotra, Ria; Sheffer, Christine E. (Frontiers in Psychology, 2019)
Socioeconomic disparities in treatment failures rates for evidence-based tobacco dependence treatment are well-established. Adapted cognitive behavioral treatments are extensively tailored to meet the needs of lower SES smokers and dramatically improve early treatment success, but there is little understanding of why treatment failure occurs after a longer period of abstinence than with standard treatment, why early treatment success is not sustained, and why long-term treatment failure rates are no different from standard treatments. We sought to understand the causes of treatment failure from the perspective of diverse participants who relapsed after receiving standard or adapted treatment in a randomized control trial. We used a qualitative approach and cognitive-behavioral framework to examine themes in responses to a semi-structured post-relapse telephone interview. The primary causes of relapse were familiar (i.e., habit, stress, unanticipated precipitating events). The adapted treatment appeared to improve the management of habits and stress short-term, but did not adequately prepare respondents for unanticipated events. Respondents reported that they would have benefited from continued support. New therapeutic targets might include innovative methods to reduce long-term treatment failure by delivering extended relapse prevention interventions to support early treatment success.